2017
DOI: 10.3390/md15020037
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 2-keto-3-deoxy-d-Gluconate Kinase and 2-keto-3-deoxy-d-Phosphogluconate Aldolase in an Alginate-Assimilating Bacterium, Flavobacterium sp. Strain UMI-01

Abstract: Recently, we identified an alginate-assimilating gene cluster in the genome of Flavobacterium sp. strain UMI-01, a member of Bacteroidetes. Alginate lyase genes and a 4-deoxy-l-erythro-5-hexoseulose uronic acid (DEH) reductase gene in the cluster have already been characterized; however, 2-keto-3-deoxy-d-gluconate (KDG) kinase and 2-keto-3-deoxy-6-phosphogluconate (KDPG) aldolase genes, i.e., flkin and flald, still remained uncharacterized. The amino acid sequences deduced from flkin and flald showed low ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…As reported, AOS has been shown to be a bifidogenic factor that promotes plant growth and enhances the growth of human endothelial cells and keratinocytes [9]. AOS can be used in medicine and healthy food because it possesses special biological activities, such as anti-tumor, anti-inflammatory, anti-coagulation, anti-oxidation, immune regulation, and blood lipid and blood sugar lowering effects [10,11]. In addition, protoplast fragments produced during the degradation of alginate can be exploited as feed for animals [12].…”
Section: Introductionmentioning
confidence: 99%
“…As reported, AOS has been shown to be a bifidogenic factor that promotes plant growth and enhances the growth of human endothelial cells and keratinocytes [9]. AOS can be used in medicine and healthy food because it possesses special biological activities, such as anti-tumor, anti-inflammatory, anti-coagulation, anti-oxidation, immune regulation, and blood lipid and blood sugar lowering effects [10,11]. In addition, protoplast fragments produced during the degradation of alginate can be exploited as feed for animals [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing interest in such simple but also in more complex enzyme cascades due to several advantages over whole-cell systems (Fessner, 2015). Such a cell-free enzyme cascade approach has been reported for alginate conversion to KDPG and further to GAP and pyruvate (Nishiyama et al, 2017). This is especially appealing for product formation from cheap and more easily available substrates and might also be considered as an alternative for KDPG synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes would constitute the metabolic pathway to convert alginate to DEH in the 5-11-6-3 and 5-25-4-2 strains ( Figure 4 ). Furthermore, the putative gene encoding 2-keto-3-deoxy-6-phosphogluconate (KDPG) aldolase, which catalyzes the cleavage of KDPG to glyceraldehyde-3-phosphate and pyruvate ( Nishiyama et al, 2017 ), was found in scaffold 1 (925,956 bp) of the 5-11-6-3 strain and in scaffold 1 (1,114,691 bp) of the 5-25-4-2 strain. However, the putative gene encoding 2-keto-3-deoxy-D-gluconate (KDG) kinase, which converts KDG to KDPG, was not found in the draft genome sequences of either strain.…”
Section: Resultsmentioning
confidence: 99%